Experimental study on driver seat vibration characteristics of crawler-type combine harvester - Xu, Lizhang; Chai, Xiaoyu; Gao, Zhipeng; Li, Yaoming; Wang, Yading (International Journal of Agricultural and Biological Engineering, 2019)
To improve the driving comfort of combine harvesters, driver seat low-frequency vibration and related driver ride-comfort problems were investigated on a Chinese CFFL-850 crawler-type full-feed combine harvester based on ISO2631. Driver vibration and driving seat transmission characteristics were measured under the following conditions: no-load idling, driving on the road, driving in the field, and simulated harvesting. The root mean square values composite vibration under four conditions were 3.63 m/s2, 2.35 m/s2, 3.34 m/s2, and 2.67 m/s2, respectively. For the same condition, the maximum root mean square scores of vibration component on driver whole-body occurred in the seat support surface (test point 1) and vertical direction (Z direction), which were 3.56 m/s2, 2.05 m/s2, 3.15 m/s2, and 2.43 m/s2, respectively. The test point 2 to test point 1 vertical-transfer function curve trends were nearly identical. Nearly all of the transfer coefficients were greater than 1 in the range of 1-50 Hz, therefore, the seat vibration attenuation performance was poor. Based on the analysis results, the driver seat structure was altered and a verification test was performed. The test results indicated that after an X-damping mechanism was installed, vibration acceleration, on the surface of the seat support under the road-driving conditions, decreased from 2.35 m/s2 to 1.68 m/s2. Under the simulated harvesting condition, the vibration acceleration decreased from 2.56 m/s2 to 1.46 m/s2. Nearly all of the seat vertical transfer coefficients were less than 1 within the frequency range of 1-80 Hz, therefore the dynamic comfort of the seat was ameliorated after structural improvement.Keywords: crawler-type combine harvester, driver seat, vibration characteristics, ride comfort, damping, structure optimumDOI: 10.25165/j.ijabe.20191202.3657Citation: Xu L Z, Chai X Y, Gao Z P, Li Y M, Wang Y D. Experimental study on driver seat vibration characteristics of crawler-type combine harvester. Int J Agric & Biol Eng, 2019; 12(2): 90–97.